Exploring Interleukin Levels in Type 1 Diabetes and Periodontitis: A Review with a Focus on Childhood - Silvia D'Agostino; Giulia Valentini; Marco Dolci (MDPI AG, 2024)
Diabetes can trigger an increase in cytokine levels leading to the production of C-reactive protein and fibrinogen. These molecules promote subclinical inflammation, causing the expression of adhesive molecules and endothelial dysfunction. Despite the lack of a comprehensive panel for single-nucleotide polymorphisms (SNPs) for interleukins associated with type 1 diabetes mellitus (T1DM), understanding the inflammatory role of SNPs is crucial because periodontitis, the sixth complication of diabetes, is influenced via these genetic variations. This review focuses on the interleukin levels in T1DM patients with and without periodontitis, with a particular focus on childhood and on SNPs when reported. A search of PubMed and Scopus identified 21 relevant studies from the past five years. Several ILs were analyzed, emphasizing that T1DM still needs to be thoroughly explored regarding an IL polymorphisms panel; however, the last five years have led to the increased independence of this condition, causing autonomous inflammatory effects, which require further investigation. The periodontitis and T1DM association in children and adolescents represents a severe gap in the literature that should be filled; this scarce presence of studies serves as motivation for further clinical research.